Review of the development of China's optical fiber communication - Zisen ZHAO (Dianxin kexue)
2016 is the 50th anniversary of Charles K Kao's proposing using optical fiber communication,the article was written to commemorate the review,in particular,the development review of China's optical fiber communication.Zhao zisen was one of the founders of Chinese optical fiber communication,the development of China's optical fiber communication was reviewed and the successful experiences and failure were absorbed.